541. Darunavir/Cobicistat/Emtricitabine/Tenofovir Alafenamide in HIV-1 Treatment Naïve Patients: Week 48 Results in Subgroups Based on Baseline Viral Load, CD4+ Count, and WHO Clinical Staging. (26th November 2018) - Spinner, Christoph D; Rashbaum, Bruce; Mcdonald, Cheryl; Mussini, Cristina; Luo, Donghan; Jezorwski, John; Brown, Kimberley; Wong, Eric Y
Abstract: Background: Darunavir/cobicistat/emtricitabine/tenofovir alafenamide (D/C/F/TAF) 800/150/200/10 mg is a once-daily, single-tablet regimen approved in Europe and under regulatory review in the United States for the treatment of HIV-1 infection. In the pivotal AMBER trial in antiretroviral treatment (ART)-naïve, HIV-1–infected adults, D/C/F/TAF achieved a high virologic response rate at Week 48 that was noninferior to control (D/C+F/tenofovir disoproxil fumarate); favorable renal/bone outcomes were seen with D/C/F/TAF vs. control. These results were consistent across age, gender, and race subgroups. Here we report Week 48 results in subgroups based on viral load (VL), CD4 + count, and WHO clinical staging of HIV/AIDS at baseline. Methods: The phase 3, randomized (1:1), blinded, noninferiority AMBER trial enrolled ART-naïve, HIV-1–infected adults. The primary endpoint was the proportion of patients with virologic response (VL <50 copies/mL; FDA snapshot) at Week 48. Adverse events (AEs) and laboratory parameters were monitored throughout the study. Results were evaluated in subgroups based on VL (≤ vs. >100, 000 copies/mL), CD4 + count (< vs. ≥350 cells/µL), and WHO clinical stage (1 vs. 2 vs. 3 vs. 4) at baseline. Results: Of the 725 patients randomized and treated, the majority had VL ≤100, 000 copies/mL (82% of patients), CD4 + count ≥350 cells/µL (72%), and WHO clinical stage 1 (84%) at baseline. Overall virologic response rates were 91.4% with D/C/F/TAF and 88.4% with control; results were similar across baseline VL, CD4 + count, and WHO clinical stage subgroups (figure). Overall rates of serious AEs, grade 3–4 AEs, and AE-related discontinuations were similar for D/C/F/TAF ( n = 17 [4.7%], n = 19 [5.2%], and n = 7 [1.9%], respectively) and control ( n = 21 [5.8%], n = 22 [6.1%], and n = 16 [4.4%]), as well as across subgroups (table). Conclusion: D/C/F/TAF achieved high (91.4%), noninferior virologic response rates vs. control (88.4%) in ART-naïve, HIV-1–infected adults. Consistent and robust efficacy and safety results were found with D/C/F/TAF vs. control based on VL, CD4 + count, and WHO clinical stage at baseline. Disclosures: B. Rashbaum, Gilead: Shareholder and Speaker's Bureau: Any financial benefit related to being a shareholder and Speaker honorarium. C. Mcdonald, Gilead: Various, Personal fees. Merck: Various, Personal fees. ViiV: Various, Personal fees. Janssen: Various, Personal fees. D. Luo, Janssen: Employee, Salary. J. Jezorwski, Janssen: Employee, Salary. K. Brown, Janssen: Employee, Salary. E. Y. Wong, Janssen: Employee, Salary.